2003
DOI: 10.1038/sj.ijo.0802398
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic measurement of mesenteric fat thickness is a good correlate with cardiovascular risk factors: comparison with subcutaneous and preperitoneal fat thickness, magnetic resonance imaging and anthropometric indexes

Abstract: OBJECTIVE: Visceral fat, notably mesenteric fat, which is drained by the portal circulation, plays a critical role in the pathogenesis of metabolic syndrome through increased production of free fatty acids, cytokines and vasoactive peptides. We hypothesize that mesenteric fat thickness as measured by ultrasound scan could explain most of the obesity-related health risk. We explored the relationships between cardiovascular risk factors and abdominal fat as determined by sonographic measurements of thickness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
132
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(142 citation statements)
references
References 20 publications
8
132
0
2
Order By: Relevance
“…However, its relatively inconsistent inter-and intraoperator reproducibilities are major shortcomings. 7,8 Dual energy X-ray absorptiometry (DEXA) provides a relatively rapid and accurate assessment of total body fat with relatively low radiation exposure but does not directly quantify VAAT. [9][10][11] Whereas CT provides more accurate estimation of VAAT, subjects are exposed to ionizing radiation, which makes it unsuitable for large-scale research.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, its relatively inconsistent inter-and intraoperator reproducibilities are major shortcomings. 7,8 Dual energy X-ray absorptiometry (DEXA) provides a relatively rapid and accurate assessment of total body fat with relatively low radiation exposure but does not directly quantify VAAT. [9][10][11] Whereas CT provides more accurate estimation of VAAT, subjects are exposed to ionizing radiation, which makes it unsuitable for large-scale research.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 With the advantages of noninvasiveness and excellent soft-tissue contrast by using different imaging parameters, MRI provides a method to measure adipose tissue safely and accurately. 8,10,[14][15][16][17][18][19][20][21][22][23][24][25]27 However, measuring the fat quantity and distribution in the abdomen by MRI is generally laborious. Two steps are required to identify the volume of VAAT.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 We have previously reported that the thickness of mesenteric fat measured on ultrasound scan was a more specific deposit of visceral fat and had a good correlation with cardiovascular risk factors in healthy individuals. 9 This study aims to explore the relationships between risk of fatty liver and mesenteric fat thickness as measured on ultrasound scan.…”
Section: Introductionmentioning
confidence: 99%